Brain Gene Expression Pattern of Subjects with Completed Suicide and Comorbid Substance Use Disorder - Cabrera, Brenda; Monroy-Jaramillo, Nancy; Fries, Gabriel Rodrigo; Mendoza-Morales, Roberto Cuauhtemoc; García-Dolores, Fernando; Mendoza-Larios, Alejandra; Diaz-Otañez, Carlos; Walss-Bass, Consuelo; Glahn, David Colin; Ostrosky-Wegman, Patricia; Fresno, Cristobal; Nicolini, Humberto (Molecular neuropsychiatry, 2019)
Although individuals with substance use disorder (SUD) are at high risk of committing suicide, most studies of postmortem gene expression exclude subjects with SUD due to the potential confounding effect of drugs in the transcriptome. Thus, little is known about the gene expression profile in suicides with SUD. The identification of altered biological processes in suicides with SUD is crucial in the comprehension of the interaction between both pathologies. We evaluated the gene expression profile in the dorsolateral prefrontal area of suicides and nonsuicides with and without SUD by microarrays. We identified 222 differentially expressed genes, predominately enriched in cell proliferation in the comparison between suicides with and without SUD. When comparing the transcriptome of suicides with SUD to nonsuicides with SUD, we identified 550 differentially expressed genes, mainly enriched in oxidative phosphorylation. Differentially expressed genes (1,417) between suicides and nonsuicides without SUD were detected. Most of them were related to mitochondrial function. Interaction between suicide and SUD seems to influence the expression of genes involved in glial proliferation and glutamatergic neurotransmission. These results highlight, for the first time, that suicides with SUD have a gene expression profile distinct from that of subjects with only one of these disorders.